2017
DOI: 10.1007/s12098-017-2344-y
|View full text |Cite
|
Sign up to set email alerts
|

Normal Peak Expiratory Flow Rate of School Children in Jabalpur, Madhya Pradesh

Abstract: Significant correlation was noted between PEFR and anthropometric parameters like height, weight and BMI. Hence, nomogram and formula created can be used in the study area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0
16

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 17 publications
0
1
0
16
Order By: Relevance
“…A presente revisão realizou um mapeamento das equações de referência disponíveis para a normalização e interpretação dos resultados no PFE em amostras pediátricas (4-18 anos), baseando-se em 13 pesquisas [12][13][14][15][16][17][18][19][20][21][22][23][24] ao redor do mundo. Este trabalho pode servir como um guia terapêutico para a tomada de decisão, considerando a análise das fórmulas preditivas disponíveis na literatura científica para diversas localidades.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…A presente revisão realizou um mapeamento das equações de referência disponíveis para a normalização e interpretação dos resultados no PFE em amostras pediátricas (4-18 anos), baseando-se em 13 pesquisas [12][13][14][15][16][17][18][19][20][21][22][23][24] ao redor do mundo. Este trabalho pode servir como um guia terapêutico para a tomada de decisão, considerando a análise das fórmulas preditivas disponíveis na literatura científica para diversas localidades.…”
Section: Discussionunclassified
“…Nestas pesquisas, embora, se observou variabilidade nas equações preditivas, percebeu-se que a altura e o sexo foram as variáveis que mais contribuíram para a predição dos resultados do PFE. Além disso, as fórmulas existentes explicaram entre 18% e 76% os valores deste desfecho, destacando-se o maior poder predição dos estudos publicados no Continente Asiático [12][13][14]20 .…”
Section: Discussionunclassified
See 2 more Smart Citations
“…6 For this purpose, evaluation of observed PEF requires knowledge of its range in healthy subjects of the same sex, age, and body size. Several studies have been conducted in developed countries to examine the normal PEF values and from India, many from the northern and eastern part of India 7,8 to date, only a few studies have been carried out to estimate the normal values of PEFR in southern Indian children. 9 In southern India, the studies that were conducted also reported an inconsistent association between PEFR values and selected anthropometric values such as height and weight.…”
Section: Introductionmentioning
confidence: 99%